Pengaruh Pemberian Klorofil Terhadap Kenaikan Kadar Hemoglobin pada Tikus Model Anemia - Faisal Hafidh; Jarot Subandono; Sri Hartati Hadinoto (Nexus Biomedika, 2014)
Background: Chlorophyll has a chemical structure similar to hemoglobin, it's just different on the central ion. Anemia is a disease in which the blood contains less hemoglobin than normal. This study aims to prove that chlorophyll can increase levels of hemoglobin and to determine whether the increase in dose of chlorophyll may increase hemoglobin. Methods: This was an experimental laboratory study with pretest and posttest control group design. Samples were female white rats, 2 to 3 months old, weighing approximately 200 grams. Thirty five samples were taken by incidental sampling and divided randomly into 5 groups, each group consisted of 7 rats. The control group was administered distilled water, in contrast the treatment group I (KPI) and II (KPII), each was treated 0.6 mg and 1.2 mg of chlorophyll once a day, while treatment group III (KPIII) and IV (KPIV), each was treated 0.6 mg and 1.2 mg of chlorophyll twice a day, respectivelly. This treatment was done for 14 days. Before acclimatization, 3 ml of rats blood was drawn from retro orbital vein. One week later, the rats blood was taken again for pretest purposes. On the day 15th, rats blood was taken again in the same way for the purposes of the posttest. Data were analyzed by Friedman test and Post Hoc Multiple Comparison (Wilcoxon) (? = 0.05). Results: Hemoglobin levels ot rats significantly increased in the chlorophyll-treated groups than in the group of no treated one. Friedman test showed significant differences between the groups treated chlorophyll and the group no treated one with p = 0.000 (p <0.05). Wilcoxon test showed no significant difference between KPI-KPII, KPI-KPIII, KPI-KPIV, KPII-KPIII, KPII-KPIV, KPIII-KPIV the value of P> 0.05 (p <0.05). Conclusion: Chlorophyll increases hemoglobin levels significantly, but increasing the dose does not provide significantly increased hemoglobin. Keywords: chlorophyll, hemoglobin, anemia